Crossing Boundaries: Acts of Citizenship among Migrant Youth in Melbourne - Mansouri, Fethi (Social Inclusion, 2014)
This paper focuses on how migrant youth in Melbourne with experience of direct or indirect migration negotiate cross-cultural engagements and tensions between family, community and the greater society in which they are supposed to participate as political subjects. It examines whether the meaning and interpretation of citizenship in Australia allows migrant youth to act as full and active citizens with all the contradictions and difficulties inherent in acting as “a bridge between two worlds”. By voicing the personalised journeys of young people dealing with uneasy questions of displacement, identity and belonging, this paper examines the complex ways through which migrant youth negotiate and in some cases bridge intercultural tensions within a multicultural society.